2012
DOI: 10.1523/jneurosci.2034-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Synaptojanin 1 Ameliorates Synaptic and Behavioral Impairments in a Mouse Model of Alzheimer's Disease

Abstract: Decades of research have correlated increased levels of amyloid β-peptide (Aβ) with neuropathological progression in Alzheimer’s disease (AD) patients and transgenic models. Aβ precipitates synaptic and neuronal anomaliesby perturbing intracellular signaling which, in turn, may underlie cognitive impairment. Aβ also alters lipid metabolism, notably causinga deficiency of phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2], a phospholipid that regulates critical neuronal functions. Haploinsufficiency of the gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 43 publications
4
59
0
Order By: Relevance
“…It should be also noted that in studies by McIntire et al, no alterations in A␤ levels were evident in 6-month-old Tg2576 mice with synj1 haploinsufficiency (6), despite the fact that they previously reported that A␤ biogenesis is modulated by PI(4,5)P 2 (11). They measured the whole brain lysates at 6 months of age, whereas we specifically quantified A␤ and amyloid plaque load from hippocampus in older mice (9 -10 months of age).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…It should be also noted that in studies by McIntire et al, no alterations in A␤ levels were evident in 6-month-old Tg2576 mice with synj1 haploinsufficiency (6), despite the fact that they previously reported that A␤ biogenesis is modulated by PI(4,5)P 2 (11). They measured the whole brain lysates at 6 months of age, whereas we specifically quantified A␤ and amyloid plaque load from hippocampus in older mice (9 -10 months of age).…”
Section: Discussionmentioning
confidence: 85%
“…Synj1 has been linked to AD and Down's syndrome (5)(6)(7). It is a phosphatase that catalyzes the dephosphorylation of the signaling phospholipid PI(4,5)P 2 , which is shown to control clathrin-mediated endocytosis (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the possible lipid-modulatory role of (20S)-Rg3, we examined the steady-state anionic phospholipid profile using conductance-based HPLC analysis (11,12,52). We found that treatment of mouse cortical neurons with (20S)-Rg3 led to increased levels of both PI(4)P and PI(4,5)P 2 (Fig.…”
Section: Modulation Of Phosphoinositide Metabolism By (20s)-rg3mentioning
confidence: 99%